The sentences of a polite killer between sharia and law (Study models) - Miqdad Haidar, Warqaa; Ashour Manse, Nahlla (International Journal of Psychosocial Rehabilitation, 2020)
Civilization has used diabolic methods that have destroyed, humiliated and tortured humanity. This paper tries to highlight two types of apparently polite crimes. It shows that moral killing is performed by participating in the crime either directly or indirectly. This is done by the perpetrators’ agreement before the crime, or by their agreement at the time of the crime without prior arrangement. After that a comparison on moral killing is carried out between our eminent Sharia and the secular laws of some Arab and Western states. Some theories and examples stated by both the Sharia and practiced laws are listed. After that two examples of moral killings, which is given a modern name polite killing, are stated. This modern name is used because it employs new methods, takes new forms, and uses several methods in killing people in the community.